IMF Survey, Volume 32, Issue 09. (IMF Survey; IMF Survey, 2003)
Over the past decade, gross cross-border capital flows have surged, not only among industrial countries but also between industrial and developing countries. What impact has this had on developing countries? A recent IMF study finds that once financial integration crosses a certain threshold, the positive effects of international capital flows can outweigh the negative effects. The authors, Eswar Prasad of the Asia and Pacific Department; Ken Rogoff, the IMF's Economic Counsellor and Director of the Research Department; Shang-Jin Wei of the Research Department; and Ayhan Kose of the Western Hemisphere Department, spoke to the IMF Survey about their study.